2018
DOI: 10.1159/000493728
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Acceptance and Expectations of a Mobile Health Application to Photograph Skin Lesions for Early Detection of Melanoma

Abstract: Background: Mobile teledermoscopy may facilitate skin self-examinations (SSEs) and further improve monitoring and detection of melanoma. Objective: To assess consumer acceptability and expectations of a mobile health app used to: (i) instruct SSE and (ii) conduct consumer-performed mobile teledermoscopy. Methods: People aged 18 years and above were invited to participate in either (i) an online survey or (ii) focus group in Brisbane, Australia. Participants were asked about their SSE practices, mobile telederm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 29 publications
0
27
0
1
Order By: Relevance
“…12 In a more recent study, the authors have found 95% ( n =84/88) of consumers would consider sending photos of their skin lesions to a medical practitioner via an app. 16 Alternatively, another variant of direct-to-consumer services is patients sending images to a medical practitioner with whom they have a known doctor–patient relationship. This would be useful for monitoring a lesion over time, or could be used to select a suspicious lesion that the patient identifies for telediagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…12 In a more recent study, the authors have found 95% ( n =84/88) of consumers would consider sending photos of their skin lesions to a medical practitioner via an app. 16 Alternatively, another variant of direct-to-consumer services is patients sending images to a medical practitioner with whom they have a known doctor–patient relationship. This would be useful for monitoring a lesion over time, or could be used to select a suspicious lesion that the patient identifies for telediagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Remotely enhancing SSE performance may require interactive apps that allow the patient to send images of concerning lesions to dermatologists or other HCPs and receive recommendations. At‐risk consumers appear to be ready to accept interactive apps 26 . When the quality of images of concerning lesions taken by users supports diagnostic interpretation, then, the app will engage users and extend health care access to at‐risk patients 27 …”
Section: Discussionmentioning
confidence: 99%
“…The Achieving Self-directed Integrated Cancer Aftercare (ASICA) Skin Checker app has been found to be feasible and acceptable for supporting SSE and triaging clinical review [30]. Studies on the preliminary assessment of diagnostic accuracy of patient-performed mobile teledermoscopy have demonstrated feasibility and acceptability for skin surveillance [31,32]. Our pilot randomised controlled trial in patients with early stage melanoma (n=100) demonstrated the feasibility of a patient-led surveillance intervention that incorporated both the ASICA app and patient-performed mobile teledermoscopy (manuscript in preparation) [33].…”
Section: Background and Rationale {6a}mentioning
confidence: 99%